WASTE BANK PROGRAM ANALYSIS THROUGH OPTIMIZATION OF THE ROLE OF INSTITUTIONS BASED ON COLLABORATIVE GOVERNANCE (CASE STUDY OF PEMATANG PUDU BERSIH WASTE BANK, MANDAU DISTRICT) - Dinda Wahyuningwidi; Irdayanti (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to determine the process of collaborative governance in implementing the waste bank program and the inhibiting factors in implementing the waste bank program in Mandau District. This study uses qualitative research methods with descriptive data assessment in the form of observation techniques, interviews, and documentation. This study uses the theory of Ansell and Gash (2007). The results of the research show that the management of the Pematang Pudu Clean Waste Bank and the government are increasing and promoting waste management for the community through the waste bank program because many people are reluctant to become waste bank customers due to a lack of knowledge regarding the waste bank mechanism.